An alternative method for identifying booms and busts in the euro area housing market - Dieter Gerdesmeier; Andreja Lenarčič; Barbara Roffia (European Central Bank (ECB), 2012)
The main aim of this paper is to apply a method based on fundamentals ─ which has already been applied in the stock market analysis ─ to detect boom/bust in the housing market, with a focus on the euro area. In this context, an underlying model is developed and tested. It turns out that the user cost rate, a demographic variable, the unemployment rate, disposable income (or disposable income per capita), the debt-to-income ratio and, finally, the housing stock are fundamental variables which significantly explain house price developments. Booms and busts are then selected as episodes when the house price index deviates excessively from the levels which would be implied by these economic fundamentals. In addition, a cross-check of the boom/bust episodes based on this method and other statistical and fundamental ones is carried out in order to substantiate the results obtained. Finally, money and credit aggregates are included in the specifications and are found to be useful in explaining boom/busts cycles in house prices.
Keywords: E37; E44; E51; 330; booms; busts; House prices; monetary and credit aggregates; Quantile Regressions